Szczegółowe wyjaśnienie:
[tex]f(x,\ y)=9ye^{-9xy+x^2}[/tex]
[tex]\dfrac{\partial f}{\partial x}=9ye^{-9xy+x^2}\cdot(-9y+2x)=(18xy-81y^2)e^{-9xy+x^2}\\\\\dfrac{\partial f}{\partial y}=9e^{-9xy+x^2}+9ye^{-9xy+x^2}\cdot(-9x)=(9-81xy)e^{-9xy+x^2}[/tex]
W pierwszej pochodnej cząstkowej skorzystałem z:
[tex](e^x)'=e^x\\\\\bigg[f\bigg(g(x)\bigg)\bigg]'=f'\bigg(g(x)\bigg)\cdot g'(x)[/tex]
W drugiej pochodnej cząstkowej skorzystałem z:
[tex]\bigg(f(x)\cdot g(x)\bigg)'=f'(x)\cdot g(x)+f(x)\cdot g'(x)\\\\(e^x)'=e^x\\\\\bigg[f\bigg(g(x)\bigg)\bigg]'=f'\bigg(g(x)\bigg)\cdot g'(x)[/tex]